Pemberdayaan Wirausaha Olahan Produk Ikan pada Masyarakat Kecamatan Mayangan Kota Probolinnggo - Abrina Anggraini, Sinar Perbawani; Wachid , Mohammad ; Boedirochminarni , Arfida (Prosiding SENTIKUIN (Seminar Nasional Teknologi Industri, Lingkungan dan Infrastruktur), 2018)
The Regional Partnership Program will be held in Mayangan Subdistrict, Probolinggo City by developing local government programs through education, economics and fisheries that prioritize community welfare. The development of community potential for fish processors needs to be improved due to lack of skills, limited employment opportunities and low entrepreneurial souls, most of whom are fishermen. Most are traditional fishermen with social and cultural characteristics that are not conducive to business progress and a decrease in the quality and quantity of local processed product resources. In this community service activity the method is carried out by means of counseling, training and mentoring to the community of Mayangan Subdistrict by empowering fish processors through the development of entrepreneurship. The development of processed fish products with quality control and food safety, especially for small and medium-sized businesses and through quality control of processed fish products will increase people's income so that government programs for public welfare can be achieved. Increased income by knowing the method of business feasibility analysis through Break Even Point and SWOT analysis can improve understanding of the acquisition of profits on processed fish products business. The results of community service activities through the Partnership Program in the Region are the formation of SMEs from not yet organized into 70 UKM from 2 villages and the formation of 14 types of UKM processed products and the formation of simple bookkeeping from 2 village.